Relevance Between Article 6 of the Universal Declaration of Human Rights and the Al-Qur’an - Solihan Makruf; Tajul Arifin; Ine Fauzia (al-Afkar, Journal For Islamic Studies, 2025)
This research is motivated by the fact that the concept of human rights, as defined in Article 6 of the Universal Declaration of Human Rights (UDHR), is relevant to the values contained in the Qur'an. This research aims to analyse the relationship between Article 6 of the UDHR, which guarantees the right to legal recognition, and the principles contained in the Qur'an. This research adopts a normative legal approach and a descriptive method of analysis. Data were collected using literature review techniques by reviewing legal documents, Qur'anic commentaries and related literature. In addition, the data was analysed using qualitative data analysis techniques. The findings of this study show that there is conceptual harmony between Article 6 of the UDHR and the teachings of the Qur'an in upholding the right to recognition as a legal subject. The findings of this study imply the need for synergy between international law and religious values in order to strengthen respect for universal human rights.